Approaches to the design of a municipal public policy evaluation model from feminism and gender (Revista revoluciones, 2024)
The public policy agenda is practically non-existent in local governments, since the majority of municipalities in Mexico are dedicated to solving recurring problems and carrying out visible actions in their administration, so the evaluation of public policies is complex due to the interests and the few years that the municipal governments have; However, there are local administrations that have been able to consolidate a comprehensive public policy agenda that even integrates approaches such as feminism, gender, and human rights. The objective of this article is to present a model for evaluating municipal public policies that has a feminist and gender perspective, in order to encourage and demonstrate that the evaluation of programs and policies in this order of government can be beneficial for the communities. administrations and the population in general.
Keywords: Evaluation; feminism; gender; public policy; municipal government